A stochastic frontier analysis of factors affecting productivity and technical efficiency of dairy farmers in the Kingdom of Eswatini - Mdluli, Bandile Banele (Stellenbosch : Stellenbosch University, 2023)
Thesis (MAgric) --Stellenbosch University, 2023.